(e)Textile New Materialities. (25th June 2021) - Almeida, Teresa
ABSTRACT: This paper explores the intersections within bodily materialism and future textiles by inquiring into embodied practices and materiality in care. By placing the body as a site of research, it centres around concepts of bodily care and the body as an ecosystem, one that is always in flux and considers the fluidity of bodies and bodily fluids, such as urine, discharge, breath and sweat, as fluids with potential to design with . It looks at how bodies are acted upon by outside forces, and explore more-than-human relations as co-creators in co-habiting the space of the body and that around it. To illustrate this, the paper introduces a series of design research artefacts that take a variety of approaches to exploring the materiality of care in the everyday. First, an eTextile toolkit that aims to create bodily awareness through hands-on engagement with textile crafting technology, then a biotextile harvesting toolkit that involves the raw material of the intimate body that explores DIYbio in the context of the home, and lastly a set of wearable living material-based explorations that recognize biomimicry and symbiotic relationships in designing for chronic stress. In embracing notions of bodily materialism, this paper explores the bodily abject, i.e. fluids and the more-than-human as crucial to engendering new modes of knowing in intimate and personal care through textile-based materials. The paper engages critically with textile design research and practice by placing material that embraces care as ambivalent at the forefront and thus challenging traditional approaches to health and care and, importantly, the design of future textiles.